EFFECT OF THE SOIL CULTIVATION METHOD ON THE MICROFLORA OF THE TRIFOLIUM PRATENSE AGROCENOSIS - Dudar І.; Shuvar І.; Ohorodnyk Н.; Korpita Г.; Pavkovych , C. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The work makes analysis of publications on the influence of cultivation method on the number of microorganisms in the soil. It is found that improving the method of the main cultivation makes it possible to enhance the agrophysical and water properties of the soil, has a positive effect on microbiological processes, provides prerequisites for expanded recovery of fertility and restoration of the natural soil formation in agrocenoses. The article describes results of the scientific research on the effect of the method of main tillage of Trifolium pratenseagrocenosis on the number of bacteria, fungi, and actinomycetes in the dark gray podzolized soils of the Western Forest Steppe and the yield of Trifolium pratense hay of the Truskavchanka variety. Three variants of the method of soil cultivation were studied, nmely I. Conventional (control) – plowing with a four-cabinet mounted with a body width of 35 cm (PLN-4-35) to a depth of 20–22 cm; II. Chisel – plowing with a chisel plow with a working width of 4.5 m (PCh-4.5) to a depth of 20–22 cm; III. Tiered – plowing with a tiered four-hull plow with a hull width of 40 cm (PYA-4-40) to a depth of 14–16 cm. For the microbiological analysis, the average samples from five individual exemplars were prepared. The main agronomically useful groups of microorganisms were selected from the soil by the method of microbiological sowing of soil extracts on solid nutrient environment: for fungi – wort-agar, for bacteria – meat-peptone agar (MPA), for actinomycetes – starch-ammonia environment. It is established that development of microorganisms depends on the method of the basic soil cultivation. The positive effect of tillage on the number of microbiota and yield of Trifolium pretense has been proven. The combined method of the main tillage (plowing with a PYA-4-40 plow) creates the most favorable environment for microorganisms: bacterial microbiota (3621.7 thousand), fungi (45 thousand) and actinomycetes (1640 thousand CFO/1 gram of completely dry soil). The highest yield of hay (115.6 c/ha) was obtained at the combined method of the main tillage, which provided a significant increase in yield as compared to the control (сonventional plowing) and chisel tillage.